2016
DOI: 10.1128/mcb.00607-15
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Thrombospondin-4 Domains Involved in Intracellular Adaptive Endoplasmic Reticulum Stress-Responsive Signaling

Abstract: bThrombospondins are a family of stress-inducible secreted glycoproteins that underlie tissue remodeling. We recently reported that thrombospondin-4 (Thbs4) has a critical intracellular function, regulating the adaptive endoplasmic reticulum (ER) stress pathway through activating transcription factor 6␣ (Atf6␣). In the present study, we dissected the domains of Thbs4 that mediate interactions with ER proteins, such as BiP (Grp78) and Atf6␣, and the domains mediating activation of the ER stress response. Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 58 publications
(105 reference statements)
4
53
0
Order By: Relevance
“…The P387-TSP-4 variant is associated with an increased risk of cardiovascular disease and myocardial infarction [15][16][17][18][19][20][21][22] and is more active than WT A387-TSP-4 in mediating cellular effects 24,37,42,49 . The region of TSP-4 molecule harboring P387 SNP appears to be important in regulation of many TSP-4 functions and was found to mediate the intracellular effects of TSP-4 50 and its effects in the nervous system 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The P387-TSP-4 variant is associated with an increased risk of cardiovascular disease and myocardial infarction [15][16][17][18][19][20][21][22] and is more active than WT A387-TSP-4 in mediating cellular effects 24,37,42,49 . The region of TSP-4 molecule harboring P387 SNP appears to be important in regulation of many TSP-4 functions and was found to mediate the intracellular effects of TSP-4 50 and its effects in the nervous system 32 .…”
Section: Introductionmentioning
confidence: 99%
“…These mutations result in mutant Thbs5 proteins that accumulate in the endoplasmic reticulum (ER) and have delayed secretion, resulting in defective chondrocytes and altered ECM composition (15-18, 22, 23, 26, 27). Similarly, we have shown that mutation of DXDXDG calcium binding sites within the T3R domains of Thbs4 results in a loss of secretion by cultured cardiomyocytes, in contrast to the robustly secreted wild-type Thbs4 protein (19).…”
mentioning
confidence: 72%
“…binding motifs within the T3R domains of the Thbs proteins are critical for their flux through the secretory pathway and deposition briefly outside the cell (15)(16)(17)(18)(19). For example, mutations in calcium binding sites in the T3R domains of the human Thbs5/ COMP gene cause skeletal dysplasia, including pseudoachondroplasia (PSACH) and multiple epiphyseal dysplasia (MED) (15,16,(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Immunoblot analysis was performed using standard methods with primary antibodies for LRRC10 (28) and ␣-sarcomeric actin (Sigma) as previously described (8,9). For coimmunoprecipitation, cardiac lysates were made in extraction buffer as described for GST pulldown assays from mice 4 wk after sham or TAC surgery and diluted in lysate incubation buffer containing rabbit IgG (Santa Cruz Biotechnology) or anti-LRRC10 (1) coupled to protein G Dynabeads (Invitrogen) and incubated overnight at 4°C.…”
Section: Experiments Used Lrrc10mentioning
confidence: 99%
“…For coimmunoprecipitation, cardiac lysates were made in extraction buffer as described for GST pulldown assays from mice 4 wk after sham or TAC surgery and diluted in lysate incubation buffer containing rabbit IgG (Santa Cruz Biotechnology) or anti-LRRC10 (1) coupled to protein G Dynabeads (Invitrogen) and incubated overnight at 4°C. Protein G beads were then washed three times with lysate incubation buffer, and immunoprecipitated proteins were eluted, resolved by SDS-PAGE, and immunoblotted as described above (9).…”
Section: Experiments Used Lrrc10mentioning
confidence: 99%